What the Book of Mormon Is (Continued) - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
An analysis of the Words of Mormon to Helaman, including Mormon's abridgment between the small and large plates of Nephi. The teachings of Benjamin, Mosiah, Abinadi, Alma, and his son, Alma the Younger. Helaman and Shiblon's writings in the book of Alma are set forth. Alma the Younger is to the Book of Mormon as Paul is to the New Testament. The book of Helaman covers fifty years of Nephite history.